ON A NEW MONOGENETIC TREMATODE HOMOSTOMA CHURA GEN. ET SP. NOV. FROM THE MARINE FISH EUTHYNNUS AFFINIS (CANTOR) WITH A NOTE ON THE FAMILY HEXOSTOMATIDAE, PRICE, 1936 - R. VISWANATHAN NUNNITHAN (Treubia, 1965)
-